Fenomena Badut Sedih : Sebuah Kajian Stakeholder Theory - Danang Nugroho; Donny Firli Ardiawan; Abiyasa Dwi Putra (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2020)
The Sad Clown phenomenon in the North Bandung area is a new and unusual phenomenon. This study aims to make observations of the existing sad clown phenomenon. This study uses a qualitative frame of mind that uses the Phenomenology method approach and the Requirements Engineering process to get a descriptive explanation from the perspective of Stakeholder Theory . This study found that there are three stakeholders who are related to the Badut phenomenon. This research is based on a new phenomenon that is happening around the Bandung area. clown / comedian (in performances and so on) ¸ a comedian is a person who likes to be funny, therefore clowns should be associated with happy things, but from the observations the existing phenomenon is a paradox, which is the Clown Phenomenon which brings a sad social context.